The implementation of the Protocol on Environmental Protection to the Antarctic Treaty : the interplay between law and environmental management - Cordonnery, Laurence (1997)
This thesis argues the need to reinforce the legal basis for environmental protection in Antarctica through an analysis of the provisions contained in the Protocol on Environmental Protection to the Antarctic Treaty. An alternative to overcome the current deficiencies of the Protocol is provided through evidenced based information documenting the spatial dimension of the issues at stake. The relevance of using Geographical Information Systems (GIS) for gathering and analysing such information is demonstrated through a case study which provides a methodology for implementing the criteria listed in the Protocol with respect to protected areas designation. The aim of the research is to integrate the analytical methods of several academic disciplines, namely international environmental law, political science, environmental studies and geographical information systems technology, in order to address the issues associated with the implementation of the Protocol on Environmental Protection to the Antarctic Treaty. The first part of the thesis analyses the legal and political obstacles to a standardised implementation of the Protocol along with the weaknesses contained in some of the provisions of the Protocol. The key role of the Committee for Environmental Protection (CEP) in the implementation process is emphasised in parallel with that of the Scientific Committee and the Commission of the Convention on the Conservation of Antarctic Marine Living Resources (CCAMLR). CCAMLR is analysed as an institutional precedent within the Antarctic Treaty System (ATS) and as a model for the institutionalisation of the CEP. The second part of this thesis analyses the potential relevance of decision support tools such as GIS to the operation of the CEP. The analysis emphasises the use of GIS for developing the new protected area system detailed in Annex V of the Protocol. It relies upon precedents within International and Antarctic Organisations which have recently adopted GIS technology for environmental management purposes. The ...